Predictors of Shoulder Degeneration in the KwaZulu-Natal Population of South Africa - Naidoo,N. (Sociedad Chilena de Anatomía, 2018)
SUMMARY: The critical shoulder angle and acromion index are conventional radiological tools employed as predictors of shoulder degeneration. As they represent the static components of glenohumeral stability, the scapulo-humeral geometry and underlying subacromial tissue appear as the resultant cause-effect factors. Consequently, the purpose of this study was to investigate the critical shoulder angle and acromion index as interrelated parameters within the South African population. The measurement of both biomechanical parameters was conducted on two-hundred and sixty (n = 260) true AP radiographs. This was a cross-sectional study that also incorporated the demographic representation of the population group which was analysed accordingly. The mean values recorded for both the critical shoulder angle (36.31±5.84º) and acromion index (0.74±0.13) suggested rotator cuff arthropathy. The results confirmed the theories of Nyffeler et al. (2006) and Moor et al. (2012) who alluded to glenoid inclination and the acromial coverage over the humeral head. A significant proportionality correlation, verified by a P value of 0.000, was established between the acromion index and critical shoulder angle which may assist to differentiate between normal asymptomatic shoulders and those with cuff disease. Furthermore, these predictors of shoulder degeneration may present as a preventative tool against tear progression.